Sistema para geração de mapas de resistência horizontal do solo a partir da força aplicada à haste sulcadora durante a operação de semeadura - Lenz, Anderson Miguel (2021)
Agricultural production is the outcome of the interaction of a series of agronomic factors separated into three major areas: physical, chemical and biological. Physical factors influence the rooting capacity of plants, which affects their ability to absorb nutrients and, consequently, the yield. The most commonly used methods to monitor the physical part of the soil are the soil core method and the resistance of the soil to penetration (RSP). The horizontal tensile force of the furrow opener and the working depth it is inserted into the soil are measures that can be correlated with soil compaction levels in a no-tillage system or any other planting system. The main objective of this dissertation was to instrument the Hoe opener, in order to evaluate the correlation among the measurements carried out by the soil core method and the resistance of the soil to penetration with the strength and depth of the rod. In the first chapter, in the 0–0.2 m layer, the interaction between horizontal force and two motion speeds of the seeder, corresponding to 1.58 and 1.87 m s–1, was evaluated at four compaction levels (0, 1, 3, 5 passes + ballast), which were artificially obtained from the passes of a farm tractor. In the 0–0.5 m layer, Pearson correlations were observed, ranging from 0.73 to 0.74 of the rod force, with the RSP; as well as correlations with the attributes monitored by the soil core method, ranging from 0.57 to 0.72. In order to expand the research, the most relevant correlations with the RSP were observed, ranging from 0.81 to 0.68. In the 0.05–0.10 m layer, lower correlation values were found, ranging from 0.52 to 0.67. At the motion speed of 1.58 m s–1 , there was a greater number of correlations, considering that, at this momentum, the mechanism that presses the rod against the soil managed to keep it at the adjusted working depth. The 0–0.05 m layer had the greatest influence on the furrow opener force. The results found indicate that, during alternative sowing, the horizontal force measurements of the Hoe opener are an alternative to monitor soil compaction. In the second chapter, the spatial correlation between the rod force and the physical attributes of the soil was evaluated in a commercial agricultural area of 7.1 ha. In this study, initially, the assortment of the Hoe opener force was carried out and subsequently 5 levels of such force were selected; considering 4 points per level, the total was 20 points. Afterwards, measurements of the soil resistance to penetration were performed, in addition to the collection of the soil core method and the yield values. From the collected data, maps of high and low sample density were generated, which led to the calculation of the Pearson correlation and the Moran index. Within the analysis of the results, it was observed that, in low-density, the Hoe force was correlated with productivity, density and total porosity. In this case, there is a need to carry out some physical intervention on the ground. In regard to the high-density data, it was observed the concentration of the furrow opener force in some bands where the sprayer’s trail is historically concentrated. For these places, the need for physical intervention in the soil was not verified. Monitoring with greater data density allows for more accurate identification of areas that need intervention, and force monitoring proves to be a useful alternative tool for tracking if there is soil compaction.